2020
DOI: 10.1016/j.redox.2019.101381
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde induces phosphorylation of dynamin-related protein 1 and mitochondrial dysfunction via elevating intracellular ROS and Ca2+ levels

Abstract: Excessive alcohol consumption impairs brain function and has been associated with an earlier onset of neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD). Acetaldehyde, the most toxic metabolite of alcohol, has been speculated to mediate the neurotoxicity induced by alcohol abuse. However, the precise mechanisms by which acetaldehyde induces neurotoxicity remain elusive. In this study, it was found that acetaldehyde treatment induced excessive mitochondrial fragmentation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 85 publications
(107 reference statements)
1
52
0
Order By: Relevance
“…To further assess the role of mtROS in mitochondrial fission, we evaluated the activation of Drp1 mediated by its phosphorylation at Ser616 in neurons treated with K5 or ST. In the case of K5, we found an increase in Drp1 phosphorylation that correlated with the observed increase in mtROS and mitochondrial fission (Figure 4(a)), in agreement with previous studies [42,71]. Moreover, we observed that MitoTEMPO significantly reduced the increase of p-Drp1 induced by K5 (Figure 4(b)), suggesting that Drp1 phosphorylation could be mediated by the mtROS induced by potassium deprivation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To further assess the role of mtROS in mitochondrial fission, we evaluated the activation of Drp1 mediated by its phosphorylation at Ser616 in neurons treated with K5 or ST. In the case of K5, we found an increase in Drp1 phosphorylation that correlated with the observed increase in mtROS and mitochondrial fission (Figure 4(a)), in agreement with previous studies [42,71]. Moreover, we observed that MitoTEMPO significantly reduced the increase of p-Drp1 induced by K5 (Figure 4(b)), suggesting that Drp1 phosphorylation could be mediated by the mtROS induced by potassium deprivation.…”
Section: Discussionsupporting
confidence: 91%
“…A possible explanation for the observed differences in Drp1 phosphorylation by K5 and ST could be the distinct signaling pathways activated by each condition. Drp1dependent mitochondrial fragmentation is regulated by several kinases, including CDK5 [84], CaMKII [82,83], ERK1/2, PKC, JNK, and p38 in different models [71,85,86]. We have previously reported that both models of apoptotic death showed differences in their molecular mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple mechanisms may play a role in the relationship between RDW and prognosis in critically ill patients with AUD. First, the alcohol metabolite, acetaldehyde, can increase the generation of free radicals, such as reactive oxygen and nitrogen, causing damage to cells or tissues (Wakabayashi, 2019; Yan and Zhao, 2020). Acetaldehyde affects the normal development of red blood cells, reduces their oxygen‐carrying capacity, and shortens the life of these cells (Waris et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Human neurons treated with ethanol showed an elevated synthesis of RONS linked to the activation of NADPH oxidase (NOX, EC 1.6.3.1), xanthine oxidase (XOX, EC 1.17.3.2), and inducible nitric oxide synthase (iNOS, EC 1.14.13.39) via acetaldehyde [152]. In neuroblastoma SH-SY5Y cells, acetaldehyde provoked mitochondrial fragmentation and cell damage in a ROS formation and calciumdependent manner by phosphorylating Drp1 (dynamin-related protein1), a key regulator of mitochondrial fission [84]. In neurovascular tissues, acetaldehyde induces oxidant production enzymes, NADPH oxidase, and iNOS [153].…”
Section: Ethanol and Oxidative Stressmentioning
confidence: 99%